Genetic diversity of Ongole Grade, Aceh, and Sumbawa cattle based on polymorphism on ND-5 fragment mitochondrial DNA using PCR-RFLP technique - SUTARNO SUTARNO; SYARIFA ZAHRAH; OKID PARAMA ASTIRIN; ELISA HERAWATI; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2019)
Abstract. Sutarno, Zahrah S, Astirin OP, Herawati E, Setyawan AD. 2019. Genetic diversity of Ongole Grade, Aceh, and Sumbawa cattle based on polymorphism on ND-5 fragment mitochondrial DNA using PCR-RFLP technique. Biodiversitas 20: 783-788. Genetic diversity is the basis of livestock breeding because it can be used as an initial improvement in livestock quality through artificial selection. This study aims to determine polymorphism in ND-5 fragment of mitochondrial DNA in Ongole Grade, Aceh, and Sumbawa cattle and their genetic diversity. The total DNA from the blood of the local cattle was extracted using the Wizard genomic DNA purification system from Promega and amplified using the PCR technique. The PCR product was then digested with HindIII enzyme using the RFLP technique to detect polymorphism. The genetic diversity of the Ongole Grade, Aceh, and Sumbawa cattle was analyzed using the formula from Nei and its genetic relationship was evaluated with the 2.02i NTSYSpc version program. Our findings showed there were polymorphisms in the ND-5 fragment of mitochondrial DNA. Digestion with HindIII restriction enzyme produces two types of haplotypes. Haplotype B is a 453 bp-sized DNA fragment that is not truncated by the HindIII enzyme, and haplotype A is a DNA fragment cut by HindIII enzyme into two with fragments of 336 bp and 117 bp. Polymorphism was found in Ongole Grade cattle, but not in Sumbawa and Aceh cattle. Haplotypes diversity in ND-5 fragments of mitochondrial DNA of Ongole Grade was 0.6250 while Sumbawa and Aceh cattle displayed no diversity of haplotypes. The genetic relationship shows that Sumbawa cattle belonged to the same cluster with Ongole Grade but separated from Aceh cattle.